2017
DOI: 10.1097/mao.0000000000001601
|View full text |Cite
|
Sign up to set email alerts
|

How Was Your Otology Training? A Survey of Recent Otolaryngology Residents

Abstract: Early exposure to ON surgeries may aid in residents' decision to pursue a fellowship in ON. The presence of fellows appears to facilitate residents' ON experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This national survey study is one of the first to objectively assess and describe the contemporary pain management strategies and opioid prescribing practices among head and neck endocrine surgeons. Furthermore, we observed relatively high survey response (34%) and completion (100%) rates compared to RR of 7.7%‐24% reported in other recently published Otolaryngology‐specific surveys, and this is a major strength of the present study. The results reveal that a majority of surgeons utilize postoperative opioids and that the associated prescribing practices vary substantially.…”
Section: Discussionsupporting
confidence: 49%
“…This national survey study is one of the first to objectively assess and describe the contemporary pain management strategies and opioid prescribing practices among head and neck endocrine surgeons. Furthermore, we observed relatively high survey response (34%) and completion (100%) rates compared to RR of 7.7%‐24% reported in other recently published Otolaryngology‐specific surveys, and this is a major strength of the present study. The results reveal that a majority of surgeons utilize postoperative opioids and that the associated prescribing practices vary substantially.…”
Section: Discussionsupporting
confidence: 49%
“…The greatest is the non‐response bias implicit in data obtained by surveys. Though we did have a fair response rate (survey response rates in otolaryngology literature range from 8% to >70%), 16,34–36 this data does not represent the opinions of every female practicing otolaryngology. The AAO‐HNS estimates that >90% of practicing otolaryngologists are members of their society; thus, it is likely that the WIO membership is a fairly accurate representation of women in otolaryngology nationwide.…”
Section: Discussionmentioning
confidence: 86%
“…30 A survey in the United States showed an average of 4.5 years before trainees felt able to perform tympanoplasty or mastoidectomy independently. 31 Data from the United Kingdom suggested that trainees in the last two years of training may still have suboptimal outcomes from tympanoplasty 32 and be unable to perform mastoidectomy independently. 33 One should note that such trainees are learning all aspects of ear, nose and throat surgery, not only otological surgery.…”
Section: Middle-ear Surgerymentioning
confidence: 99%